Electric scooters a growing public health problem - Czekaj, Aleksandra; Dubel, Robert; Ruszel, Kinga; Dubel, Julia; Namroży, Natalia (Quality in Sport, 2022)
Electric scooters have recently become the most popular means of transport chosen to move around urban agglomerations. It is estimated that by the end of 2024, the number of scooters on the roads around the world will increase by about 600% compared to 2019. Easy access to rental and low purchase price significantly convince many people around the world to use this form of transport. This review article aims to show what a serious health risk a scooter can be. The issue of the most common injuries related to the use of this type of vehicle was also discussed. The growing popularity of electric vehicles brings with it the possibility of recording more and more cases of injuries related to electric scooters. Numerous violations of road rules and riding a scooter under the influence of alcohol, in most cases without protective clothing, significantly contribute to the formation of high-energy injuries in victims.